Observations of migrant exchange and mixing in a coral reef fish metapopulation link scales of marine population connectivity - Horne, J.; Van Herwerden, L.; Abellana, S.; McIlwain, Jennifer (Oxford Journals, 2013)
Much progress has been made toward understanding marine metapopulation dynamics, largely because of multilocus microsatellite surveys able to connect related individuals within the metapopulation. However, most studies are focused on small spatial scales, tens of kilometers, while demographic exchange at larger spatial scales remains poorly documented. Additionally, many small-scale demographic studies conflict with broad-scale phylogeographic patterns concerning levels of marine population connectivity, highlighting a need for data on more intermediate scales. Here, we investigated demographic recruitment processes of a commercially important coral reef fish, the bluespine unicornfish (Naso unicornis) using a suite of mitochondrial DNA (mtDNA) and microsatellite markers. Sampling for this study ranged across the southern Marianas Islands, a linear distance of 250 km and included 386 newly settled postlarval recruits. In contrast with other studies, we report that cohorts of recruits were genetically homogeneous in space and time, with no evidence of temporally stochastic sweepstakes reproduction. The genetic diversity of recruits was high and commensurate with that of the adult population. In addition, there is substantial evidence that 2 recruits, separated by 250 km, were full siblings. This is the largest direct observation of dispersal to date for a coral reef fish. All indications suggest that subpopulations of N. unicornis experience high levels of demographic migrant exchange and metapopulation mixing on a spatial scale of hundreds of kilometers, consistent with high levels of broad-scale genetic connectivity previously reported in this species. © The American Genetic Association. 2013. All rights reserved.